Influence of psoas muscle area on mortality following elective abdominal aortic aneurysm repair. Issue 4 (31st January 2019) - Waduud, M. A.; Wood, B.; Keleabetswe, P.; Manning, J.; Linton, E.; Drozd, M.; Hammond, C. J.; Bailey, M. A.; Scott, D. J. A.; ,
Abstract : Background: The effect of sarcopenia based on the total psoas muscle area (TPMA) on CT is inconclusive in patients undergoing abdominal aortic aneurysm (AAA) intervention. The aim of this prospective cohort study was to evaluate morphometric sarcopenia as a method of risk stratification in patients undergoing elective AAA intervention. Methods: TPMA was measured on preintervention CT images of patients undergoing elective endovascular aneurysm repair (EVAR) or open aneurysm repair. Mortality was assessed in relation to preintervention TPMA using Cox regression analysis, with calculation of hazard ratios at 30 days, 1 year and 4 years. Postintervention morbidity was evaluated in terms of postintervention care, duration of hospital stay and 30‐day readmission. Changes in TPMA on surveillance EVAR imaging were also evaluated. Results: In total, 382 patient images acquired between March 2008 and December 2016 were analysed. There were no significant intraobserver and interobserver differences in measurements of TPMA. Preintervention TPMA failed to predict morbidity and mortality at all time points. The mean(s.d.) interval between preintervention and surveillance imaging was 361·3(111·2) days. A significant reduction in TPMA was observed in men on surveillance imaging after EVAR (mean reduction 0·63(1·43) cm 2 per m 2 ; P < 0·001). However, this was not associated with mortality (adjusted hazard ratio 1·00, 95 per cent c.i. 0·99 to 1·01; P = 0·935). Conclusion: TPMA is not a suitable risk stratification tool for patients undergoing effective intervention for AAA. Abstract : The total psoas muscle area (TPMA), as a measure of sarcopenia and frailty, has been demonstrated previously to be a potential method of risk stratification in surgical patients. In this study, TPMA did not appear to be associated with mortality and morbidity in patients undergoing elective abdominal aortic aneurysm intervention. Therefore TPMA may not be a suitable method of risk stratification for routine clinical practice. Not predictive